2017
DOI: 10.1186/s13643-017-0594-4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for acute stroke management in Africa: a systematic review of the evidence

Abstract: BackgroundThe past decades have witnessed a rapid evolution of research on evidence-based acute stroke care interventions worldwide. Nonetheless, the evidence-to-practice gap in acute stroke care remains variable with slow and inconsistent uptake in low-middle income countries (LMICs). This review aims to identify and compare evidence-based acute stroke management interventions with alternative care on overall patient mortality and morbidity outcomes, functional independence, and length of hospital stay across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 64 publications
0
47
0
Order By: Relevance
“…Stroke case-fatality rates in SSA are the highest in the world ranging from 21-47% in various studies [66,68,69], compared to 17-30% in high-income countries [70], and almost double for hemorrhagic stroke compared to ischemic stroke [67,68]. A few studies have demonstrated overall positive patient outcomes following acute stroke care interventions in Africa [71]. Given that hypertension is the single most important preventable risk factor for stroke in SSA [6,66], its optimal control should be the main focus to help reduce stroke occurrence.…”
Section: Stroke (Cerebrovascular Disease)mentioning
confidence: 99%
“…Stroke case-fatality rates in SSA are the highest in the world ranging from 21-47% in various studies [66,68,69], compared to 17-30% in high-income countries [70], and almost double for hemorrhagic stroke compared to ischemic stroke [67,68]. A few studies have demonstrated overall positive patient outcomes following acute stroke care interventions in Africa [71]. Given that hypertension is the single most important preventable risk factor for stroke in SSA [6,66], its optimal control should be the main focus to help reduce stroke occurrence.…”
Section: Stroke (Cerebrovascular Disease)mentioning
confidence: 99%
“…Similar to other resource‐poor regions, recent research indicates access and delivery of quality and evidence‐based stroke care in Africa is limited and often poor . Studies in Ghana, Senegal and Congo further exemplify the limited nature of access to quality and evidence‐based stroke care in LMICs.…”
Section: Introductionmentioning
confidence: 95%
“…For example, it is estimated that up to 8.4 million deaths are recorded annually in LMICs as a result of compromised quality of care . Within the context of stroke care, a paradoxical situation exists where delivery of quality and evidence‐based care for optimal patient outcomes is relatively limited and poor in LMICs compared to high‐income countries (HICs), although about 80% of the entire global burden of stroke is reported from LMICs . This burden has been largely attributed to the poor quality of care delivered in those settings and the low uptake of evidence‐based practice .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations